The American University of Beirut and its role in the formation of the political elite in Jordan: The Prime Minister position 1944-2016 as a model - Abu Seeni, Abdalhameed Mohammad (Al-Adab Journal, 2022)
This study aims at investigating and analyzing the influence made the American University of Beirut on the formation of the Jordanian political elite. The sample of this study contains ten names of former prime ministers who graduated from this university and served as prime ministers between 1944-2016.The study has employed the descriptive analytical approach by studying Jordanian and non-Jordanian documents, newspapers and the official websites.The researchers found that United States of America have managed to impose its soft power and its own agendas by attracting a number of students to pursue their higher education in the AUP; by this, USA was able to prepare them to be the future leaders having liberal thought and it was also able to let ten of them be prime ministers.The findings showed that there should be a systematic mechanism for allowing real elites that have a clear national vision and mission based on well-established awareness and devotion towards the Jordanian national interestsregrardless of the other countries’ agendas in the Arab region.